Facile synthesis of amorphous Ni(OH)2 for high-performance supercapacitors via electrochemical assembly in a reverse micelle. (20th August 2015) - Hu, Liwen; Yu, Zhijing; Hu, Zongqian; Song, Yang; Zhang, Feng; Zhu, Hongmin; Jiao, Shuqiang
Abstract: The specific and unique amorphous nickel hydroxide nanostructures were synthesized via a simple and straightforward electrochemical way. By simply tuning the soft templates and applying a suitable current density, a specific and unique microstructure is obtained. The diameter of the Ni(OH)2 nano-sphere is greatly influenced by the current density, the sample obtained at 1 mAcm −2 is about 200 nm while the size of that assembled at 6 mAcm −2 is less than 20 nm. However, the Ni(OH)2 film prepared at the current density of 2 mAcm −2 showed the best electrochemical performance for the highly porous surface morphology which contributed to the uniform morphology obtained at this current density. The maximum specific capacitance can be achieved as high as 1460Fg −1 in 2 M NaOH at the scan rate of 2mVs −1 . Such impressive electrochemical properties can be ascribed to the highly porous microstructures and disorder of the amorphous phase which was considered for the better accommodation of repeated volume changes associated with doping-undoping process. The high specific capacitance and remarkable rate capability of amorphous transition metal oxides nanostructures show broad prospect for potential applications in energy conversion and storage devices.